Analysis of single switch step up DC-DC converter with switched inductor-switched capacitor cells for PV system - Gnanavadivel, J.; Kalarathi, M.; Prakash, K. (International Journal of Applied Power Engineering (IJAPE), 2024)
The presented work exhibits high gain and increased efficiency for DC-DC converter. Additionally, this topology significantly improves the voltage conversion ratio when compared with other DC-DC converters reported recently. The non-existence of high frequency transformer ensures compactness and low cost and henceforth, it is apt for clean energy applications. The analysis of the high gain converter in steady state is carried out in continuous conduction mode (CCM). Initially, the proposed converter performance is analyzed using MATLAB/Simulink platform and prototype of the same with a power rating of 200 V, 100 W is built and tested. The reliability and robustness of the converter is perceived from the experimental results and peak efficiency achieved is around 93%.